Successful short passing frequency of defenders differentiates between top and bottom four English Premier League teams - Adams, D.; Morgans, R.; Sacramento, J.; Morgan, S.; Williams, M. D. (International Journal of Performance Analysis in Sport, 2013)
Dominating ball possession during football matches may be a feature of successful English Premier League (EPL) teams. Yet, supporting evidence remains unclear. This study aimed to identify which performance indicators falling under the umbrella of possession separate teams that finish at the top versus teams that finish at the bottom of the EPL. Aggregated technical data for defending, midfield and attacking units obtained from all EPL matches played in one season were analysed. Decision tree induction was applied to a training dataset (N = 149). The final model involved five splits (Rsquare = 0.662). The variable with the largest contribution to the final decision tree model was total successful short passes made by defenders (G2 = 115). The second largest contribution was successful passes made in the opposition half by midfielders (G2 = 13), the third variable that contributed was unsuccessful passes opposition half made by defenders (G2 = 8). All other selected variables made negligible contributions